MEDIA RESPONSES TO US CORPORATE AND GLOBAL ENVIRONMENTALIST PROJECTS IN AMAZÔNIA, 1928-2000 - Zirker, Daniel (Revista Brasileira de Estudos de Defesa, 2014)
Military, environmental and corporate US and European interests were focused on Amazônia after 1926. This analyzes attempts to extract resources, US-Brazilian military crises, and the media on resistance to corporate and environmental projects in Amazônia up to the end of the 1990s. Keywords: Projects in Amazônia. America. Media. Resources extraction. Brazilian’s military.